Use, Abuse, and Associated Impacts of Alcohol on Health and Crimes in Nepal - Gautam, Lata; Bohara, Apil; Satyal, Jaya; Grela, Agatha (Annapurna Journal of Health Sciences, 2023)
Alcohol is a socially acceptable and widely available drink in most countries. Its excessive consumption is linked to various health issues, increase in crime rate and even loss of life. This puts heavy strain in low-income countries like Nepal where full medical facilities are still out of reach for most of the population. Therefore, in this article, we have provided an overview of (i) the effect of alcohol on public health; (ii) trend data on alcohol seizures; (iii) alcohol (including methanol) positive forensic cases; and (iv) other alcohol associated crimes. Our analysis is drawn from a range of data types and sources, triangulating the collected data with alcohol specific academic and grey literature, a survey with students and insights from stakeholder engagements in Nepal. We have shown that alcohol has been associated with a range of health-related issues and crime types in Nepal. For example, alcohol was the most mentioned compound in the student survey (50.7%; n=418) followed by other drugs in Drugs Facilitated Sexual Assault cases. We have also discussed issues with adulteration, surrogates and sub-standard alcohol, highlighting the need for strict monitoring, regulations and extra vigilance about quality control of alcohol in circulation. This should be supported by public awareness campaigns on the use, abuse and impacts of alcohol.